2004
DOI: 10.1002/adma.200306331
|View full text |Cite
|
Sign up to set email alerts
|

High‐Efficiency, Saturated Red‐Phosphorescent Polymer Light‐Emitting Diodes Based on Conjugated and Non‐Conjugated Polymers Doped with an Ir Complex

Abstract: Recently, organic light-emitting diodes (OLEDs) based on phosphorescent dyes have attracted increasing attention due to their potential application in full-color flat panel displays. Owing to the strong spin±orbital mixing of heavy-metal ions in phosphorescent complexes, both singlet and triplet excitons can be fully utilized, [1±5] creating the possibility for electrophosphorescent dye doped devices to reach an internal quantum efficiency of 100 %. Baldo et al.[5] first demonstrated extremely high-efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
143
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(147 citation statements)
references
References 32 publications
3
143
1
Order By: Relevance
“…Moreover, photogenerated exciton in D102 may be relaxed by transferring its energy to P3HT, since the energy levels of P3HT are contained within those of D102, which disfavors good device performance. [42] Figure 4D schemes the energy levels after treating the dyemodified TiO 2 film with Li salt and TBP. For N719, the treatment leads to a slight increase in the LUMO energy level (3.21 eV), while the HOMO level (5.06 eV) is retained.…”
Section: à2mentioning
confidence: 99%
“…Moreover, photogenerated exciton in D102 may be relaxed by transferring its energy to P3HT, since the energy levels of P3HT are contained within those of D102, which disfavors good device performance. [42] Figure 4D schemes the energy levels after treating the dyemodified TiO 2 film with Li salt and TBP. For N719, the treatment leads to a slight increase in the LUMO energy level (3.21 eV), while the HOMO level (5.06 eV) is retained.…”
Section: à2mentioning
confidence: 99%
“…[20,21] Moreover, PFs can be used as host materials to generate other colors through energy transfer to lowerenergy emitters in blends with other conjugated polymers, fluorescent dyes, and organometallic triplet emitters. [5][6][7][8][9][10][22][23][24][25] Consequently, PFs can function as both the host and the blue emitter in white-light-emitting PLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…The difference between the two Ir complexes is the homoleptic one for Ir(piq) 3 O/Al), it was confirmed that the electron-transporting host BAlq outperforms the rest of the host materials [156]. (piq) 2 Ir(acac) can also be employed in solution processed [157] device ITO/PEDOT:PSS/PVK/blends/Ba/Al, where the active layer contains a blend of electron-transporting 2-(4-biphenyl)-5-(4-tert-butylphenyl)-1,3,4-oxadiazole (PBD) or 3-phenyl-4-(1′-naphyl-5-phenyl-1,2,4-triazole) (TAZ), and one of three kinds of polymeric host material: poly-9,9-dioctylfluorene (PFO), polyvinylcarbazole (PVK), and polyfluorene-p-substituted triphenylamine (PFTA). Among them, PFTA blended with PBD is the best device, having EQE near 12 %, which is higher than that of (piq) 2 Ir(acac) OLED with the thermal evaporation process.…”
Section: Red Phosphorescent Materialsmentioning
confidence: 51%